TRENDS ANALYSIS IN GIG ECONOMY - Milosevic, Dragan; Ilic, Dejan; Popovic, Jovanka (Journal of Economic Development, Environment and People, 2021)
This paper aims to research the main characteristics and trends of the freelancer’s market in temporary and occasional jobs in the Digital economy. The research was conducted by analyzing the content of reports of companies that hire freelancers, consulting companies and blogs of experts. The Digital economy is one of the results of the widespread application of information and communication technologies (ICT) that have influenced the transformation of the business model. Widespread application of ICT increased the flexibility of the work environment from the perspective of the place and time of work, as well as the way of engagement of the workforce. The application of ICT has expanded the scope and range of services available in today’s market of temporary and occasional jobs. Contemporary companies in the Digital economy are increasingly focusing on their core competencies, leaving other jobs to external associates. The Gig economy refers to the engagement of labour in temporary and occasional jobs. Of the total number of employees in the USA during 2020, 36% worked as freelancers. Freelancers, during 2020, generated total revenue of US 1.2 trillion. Also, it is important to point out that a certain percentage of freelancers, currently, realize additional jobs in this way, but that there is a noticeable increase in the number of freelancers who accept this model of employment as the only way of permanent employment. Also, further growth in the number of freelancers in the world is predicted.